ANALISIS KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH RIGHT ISSUE - Anastasia Krizia (2021)
The purpose of this study was conducted to determine the differences in the company's financial performance before and after the rights issue. In this study, the financial performance uses four variables, namely profitability (ROE), liquidity (CR), leverage (DER), and business activities (TATO). This study uses 45 companies that carry out rights issues listed on the Indonesia Stock Exchange in 2015-2018, with the final sample of the study is 28 companies. This study uses secondary data with a sample method using purposive sampling. The data analysis technique used in this study was the paired-sample t-test and the Wilcoxon signed-rank test, with the help of the SPSS 25 application. The results of these tests indicate that (1) the profitability before and after the right issue is not different, (2) the liquidity before and after the right issue is not different,(3) the leverage before and after the right issue is different, (4) the business activities before and after the rights issue is different. Keywords : Right issue, profitability, liquidity, leverage, and business activities